2012
DOI: 10.1038/nchembio.1084
|View full text |Cite
|
Sign up to set email alerts
|

A selective inhibitor of EZH2 blocks H3K27 methylation and kills mutant lymphoma cells

Abstract: EZH2 catalyzes trimethylation of histone H3 lysine 27 (H3K27). Point mutations of EZH2 at Tyr641 and Ala677 occur in subpopulations of non-Hodgkin's lymphoma, where they drive H3K27 hypertrimethylation. Here we report the discovery of EPZ005687, a potent inhibitor of EZH2 (K(i) of 24 nM). EPZ005687 has greater than 500-fold selectivity against 15 other protein methyltransferases and has 50-fold selectivity against the closely related enzyme EZH1. The compound reduces H3K27 methylation in various lymphoma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
577
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 689 publications
(608 citation statements)
references
References 44 publications
24
577
1
4
Order By: Relevance
“…15,[19][20][21][22][23][24] Notably, its molecular or pharmacological inhibition leads to the reversal of the malignant phenotype. [24][25][26][27][28][29] Collectively, these findings demonstrate a role of EZH2 as a potential prognostic marker and therapeutic target in cancer. We and others have recently reported that (i) as compared with the normal myoblasts and muscle tissues EZH2 is markedly overexpressed in RMS 30,31 and (ii) EZH2 downregulation in vitro leads to myogenic-like differentiation of an embryonal RMS cell line.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…15,[19][20][21][22][23][24] Notably, its molecular or pharmacological inhibition leads to the reversal of the malignant phenotype. [24][25][26][27][28][29] Collectively, these findings demonstrate a role of EZH2 as a potential prognostic marker and therapeutic target in cancer. We and others have recently reported that (i) as compared with the normal myoblasts and muscle tissues EZH2 is markedly overexpressed in RMS 30,31 and (ii) EZH2 downregulation in vitro leads to myogenic-like differentiation of an embryonal RMS cell line.…”
Section: Introductionmentioning
confidence: 71%
“…26,27,29 In the attempt to evaluate the effect of pharmacologic inhibition of EZH2, we have used DZNep, which has been already shown to induce FBXO32 expression in cancer cells 25,28,40,66 in parallel with an EZH2 catalytic inhibitor, MC1945. 33,34 Both pharmacological treatments phenocopied the effects of genetic inhibition of EZH2 in vitro enhancing the apoptotic rate of fusion-positive alveolar RMS cells, upregulating FBXO32 and downregulating Myogenin.…”
Section: (Student's T-test) (B) Ezh2mentioning
confidence: 99%
“…As the administered dose of compound correlates with reduction in H3K27me3 levels in tumor tissue and of tumor growth, the clinical use of such inhibitors for cancers in which EZH2 is genetically altered is relevant. 88,89 Interestingly, Kim and colleagues discovered that EZH2 enhances STAT3 activation by trimethylating lysine180 in STAT3, and it does so preferentially in glioma stem-like cells. 90 The use of the EZH2 inhibitor 3-deazaneplanocin A (DZNep) 91,92 and a highly selective EZH2 inhibitor GSK126 93 decreases STAT3 activation in glioma stem-like cells.…”
Section: Kmts and Prmtsmentioning
confidence: 99%
“…La molécule EPZ005687 se lie à EZH2 mais également à une forme mutante de la protéine (Y641). Elle présente une sélectivité 500 fois plus importante pour EZH2 que pour d'autres méthyltransférases [40]. Une autre molécule, EPZ-6438, qui présente un mécanisme d'action et une spécificité similaire à celle d'EPZ005687, a pu être testée dans des essais cliniques de phase I et II chez des patients atteints de tumeurs rhabdoïdes 4 malignes et de lymphomes de type B avancés.…”
Section: Rôle Suppresseur De Tumeur D'ezh2unclassified